Analysis of Budgetary Accounting Accountability to Improve the Quality of Financial Reports - Bahrun; Ahmad Juanda; Driana Leniawati (LP2M IAIN Palopo, 2026)
Accountability in budget management is critical to enhancing the integrity of financial statements at private colleges. The purpose of this research is to examine budget accounting responsibility and how it might enhance the integrity of financial statements by utilising an integrated Accounting Information System (AIS). A qualitative case study technique was used in the research methodologies. Data were gathered through interviews, and document analysis. The findings revealed that effective budget accountability has a vital role in boosting the openness of budget management, resulting in more accurate, relevant, and timely financial reporting. This study recommends that the Islamic University in Baubau City, a private university, improve budget management by implementing an integrated accounting information system to improve accountability and financial statement quality, as well as strengthen public trust in the institution